Modeling and empirical evidence of the impact of implementation of sugar sweetened-beverages tax to reduce non-communicable diseases prevalence: a systematic review - Firdaus, Safira; Andarwulan, Nuri; Hariyadi, Purwiyatno (Frontiers in Nutrition, 2024)
We marked the revisions by highlighting them in yellow and providing responses in the form of comments on certain paragraphs. There are terms that have been changed, namely excise tax to just 'tax' to prevent misunderstanding in interpreting the study. We updated several typos in the writing, as well as references, conclusions, abbreviations, and bibliographies.Reviewer 1 Suggestion: Conceptualization of results: discussion based on regional variation and policy implications A: we have added a regional-based discussion, especially based on World Bank Group income and policy implications and recommendations in the sub-chapter "3.3 Is The SSB Tax Effective to Reduce the Prevalence of NCDs?" Suggestion: Clarity in presentation A: we have aligned the way of presenting the results starting from effect size, standard deviation, confidence interval, and unconfidence interval, so that it is easier to interpret. we also revised this in the supplementary material